Dry Eye and Phacoemulsification Cataract Surgery: A Systematic Review and Meta-Analysis - Lu, Qiang; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2021)
Purpose: To evaluate whether dry eye deteriorates after phacoemulsification cataract surgery, and to explore the influential factors. Methods: Studies published before February 2020 indexed on PubMed and the Cochrane Central Register of Controlled Trials were retrieved. A meta-analysis, including meta-regression, a sensitivity analysis, and a subgroup analysis, were performed. Results: Twenty studies with 2247 eyes were included in the meta-analysis, dry eye-related parameters were investigated preoperatively and 1 month postoperatively. Patients with pre-existing meibomian gland dysfunction (MGD) had worsened subjective symptoms of dry eye (1.31, 95% confidence interval (CI) [0.66, 1.95], P < 0.0001), a reduced tear break-up time (BUT) (−2.27, 95% CI [−2.66, −1.88], P < 0.0001), and a worse corneal fluorescein staining (CFS) score (0.75, 95% CI [0.5, 1.0], P < 0.0001) after phacoemulsification cataract surgery, whereas in the general population, the subjective symptoms score and CFS remained unchanged and BUT decreased slightly after surgery. Patients without diabetes showed significantly reduced total tear secretion after phacoemulsification cataract surgery (−1.25, 95% CI [−1.62, −0.88], P < 0.0001). Conclusion: Dry eye generally remained unchanged 1 month after phacoemulsification cataract surgery. Notably, worsened symptoms and signs of dry eye were observed more frequently in patients with pre-existing MGD. Patients without diabetes were more susceptible to reduced tearing postoperatively.